INNV-13. A NOVEL TELEGRAM CHAT APPLICATION BASED BOT (FLORENCEBOT) FOR BRAIN TUMOUR AFFECTED PATIENTS. (11th November 2019) - Puri, Abhishek; Sandeman, Kyle
Abstract: The discoverability of reliable information online is difficult. As the network grows exponentially, unregulated content has the potential to cause harm. Telegram is a popular mainstream chat application. It allows automated software called bots that interact passively with an individual. Florence bot is unique in this space for the patient support; for those affected by brain tumours. It has been developed in PHP and hosted privately by the developer. Florence links to physician generated content (hosted externally on a blogging website) such as introduction, signs and symptoms of brain tumours and various treatment options along with their side effects. The content generates "web view" in Telegram itself, preserving written and multimedia formats. It ensures minimal overheads on the bot, making it responsive. It links to brain tumour channel (automated streamed information working as a public broadcast) and physician-administered support group. A physician designed bot is preferable to a third party mobile application to ensure the accurateness of information. No user-related information is available to bot developers as it does not have tracking and advertising elements; hence safeguards users privacy. It is more accessible and cheaper to deploy than a mobile application as it uses an instant messaging app as its container, which works across computing platforms. Florence bot is expected to bridge the gap for reliable information and real-time support independent of geographical limitations.